Kontribusi Relawan dalam Pendidikan Non Formal: Studi Kasus Sekolah Nusantara di Rusunawa Lingkungan Urban Marginal - Ainaya Diyan Fatichah; Rendi Agung Febrianto (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
Education is a key pillar of national development, as mandated by the 1945 Constitution of Indonesia. However, significant disparities persist in public housing (rusunawa) areas, including limited learning facilities, low parental engagement, and poor socio-economic conditions. Non-formal, community-based education has emerged as a viable solution. This study explores the role of the Senyum Anak Nusantara (SAN) Community in implementing Sekolah Nusantara at Rusunawa Sawah Besar, Semarang. Using a descriptive qualitative case study approach, the research involved six informants—community organizers, volunteer teachers, and students. Data were gathered through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, with triangulation to ensure validity.Findings indicate SAN contributes at three levels: (1) planning, by identifying children’s learning needs and developing a contextual curriculum; (2) implementation, through interactive STAM-based (Science, Technology, Art, and Morality/Mathematics) learning with 37 volunteers and 12 rotating instructors for 40 students; and (3) sustainability, via self-funding, material provision, and graduation ceremonies. Additionally, SAN fosters emotional connections with children and increases parental awareness of education’s value. In summary, SAN serves as a catalyst for inclusive, contextual, and sustainable non-formal education, supporting SDG Goal 4 on quality education.